Rational use of antimicrobials in the treatment of upper airway infections - Santiago Alfayate Miguélez; Luis Garcia‐Marcos (Jornal de Pediatria (Versão em Português), 2020)
Objective: To analyze the main cause of the irresponsible use of antibiotics at the pediatric level in a very frequent, usually self‐limited, and typically viral condition: upper airway respiratory infections. Sources: Different databases were searched using specific terms related to resistance to antibiotics, upper airway respiratory infections, and pediatrics patients. Summary of the findings: Effectiveness varies depending on the place, the form of intervention, and the resources used. Multiple interventions appear to be more effective. The foundations of treatment are training in technical aspects and in communication skills for the prescribers, and having enough time for each patient; and training through the health clinic and the media for patients/parents. Deferred prescription and the use of rapid diagnostic tests in the primary care setting have been shown to be effective. A fluid relationship based on trust between clinicians and parents/guardians is one of the keystones. Conclusions: Any project that seeks to be totally effective must include a health authority, which in addition to helping implement these measures, has the firm intention of drastically reducing the use of antibiotics in animals and in the environment, as well as favoring research into new antimicrobials. Resumo: Objetivo: Analisar a principal causa do uso irresponsável de antibióticos em nível pediátrico de doenças muito frequentes, normalmente autolimitadas e virais: infecções respiratórias das vias aéreas superiores. Fontes: Diferentes bases de dados foram pesquisadas com termos específicos relacionados à resistência a antibióticos, infecções respiratórias das vias aéreas superiores e pacientes de pediatria. Resumo dos achados: A eficácia varia, depende do local, da forma e dos recursos usados. As formas de múltiplas intervenções parecem mais eficazes. O treinamento em aspectos técnicos e habilidades de comunicação para médicos e tempo suficiente para cada paciente, além do treinamento por meio da clínica e da mídia para pacientes/pais, são a base da eficácia. Prescrições de uso posterior e testes de diagnóstico rápido no ambiente de cuidado primário mostraram ser eficazes. Uma relação de confiança entre médicos e pais ou responsáveis é uma das pedras angulares. Conclusões: Qualquer projeto que busque ser completamente eficaz deve incluir uma autoridade em saúde, que, além de ajudar a implantar as medidas nos pacientes, tem a sólida intenção de reduzir drasticamente o uso de antibióticos em animais e no meio ambiente, além de favorecer a pesquisa sobre novos antimicrobianos. Keywords: Antibiotic resistance, Upper airway infections, Children, Palavras‐chave: Resistência antibiótica, Infecções das vias aéreas superiores, Crianças